Porphyra-334, a mycosporine-like amino acid, attenuates UV-induced apoptosis in HaCaT cells - Suh Sung-Suk; Oh Se Kyung; Lee Sung Gu; Kim Il-Chan; Kim Sanghee (Acta Pharmaceutica)
The main aim of the current research was to study the effect of porphyra-334, one of mycosporine-like amino acids (MAAs), well known as UV-absorbing compounds, on UVinduced apoptosis in human immortalized keratinocyte (HaCaT) cells. Due to their UV-screening capacity and ability to prevent UV-induced DNA damage, MAAs have recently attracted considerable attention in both industry and research in pharmacology. Herein, human HaCaT cells were used to determine the biological activities of porphyra- 334 by various in vitro assays, including proliferation, apoptosis and Western blot assays. The proliferation rate of UV-irradiated HaCaT cells was significantly decreased compared to the control group. Pretreatment with porphyra- 334 markedly attenuated the inhibitory effect of UV and induced a dramatic decrease in the apoptotic rate. Expression of active caspase-3 protein was increased in response to UV irradiation, while caspase-3 levels were similar between cells treated with porphyra-334 and the non-irradiated control group. Taken together, our data suggest that porphyra-334 inhibits UV-induced apoptosis in HaCaT cells through attenuation of the caspase pathway.